Literature review of tri-colored bat natural history with implications to management - McCoshum, Shaun M.; Pratt, Erica L.; Lent, Kayla C.; Boisen, Ellie M. (Frontiers in Conservation Science, 2023)
In the past decade, caverniculous bat populations have plummeted due to White-nose syndrome (WNS). Tri-colored bat (Perimyotis subflavus) populations have declined drastically in areas where WNS has been found, leading to the decision to protect tri-colored bats under the federal Endangered Species Act in the United States. At this time, there has not been a thorough review of the literature, nor a concise summary of the tri-colored bat’s life history, diet, threats, or habitat preferences. This absence creates more work for policy makers, federal “Take” permit applicants, and conservationists to find, access, and review critical details of tri-colored bats. A major point of confusion stems from the multiple common names and genera tri-colored bats have been classified under since it was first described a century and a half ago. To address the lack of concise summary, we scoured the scientific literature and compiled nearly a century of data to provide a robust review of the ecology, life history, winter and summer habitats, as well as created maps and figures showing counties where studies have occurred, white-nose syndrome is present, and where bats have been documented. Additionally, this paper highlights data gaps and suggests future research topics that may better inform conservation and management decisions for tri-colored bats.